Virological Passive Surveillance of Avian Influenza and Arboviruses in Wild Birds: A Two-Year Study (2023–2024) in Lombardy, Italy - Maria Cristina Rapi; Ana Maria Moreno Martin; Davide Lelli; Antonio Lavazza; Stefano Raimondi; Marco Farioli; Mario Chiari; Guido Grilli (Microorganisms)
Avian influenza (AI), caused by Alphainfluenzavirus (family Orthomyxoviridae), poses significant threats to poultry, biodiversity, and public health. AI outbreaks in poultry lead to severe economic losses, while highly pathogenic strains (HPAIVs) severely impact wild bird populations, with implications for biodiversity and potential zoonotic risks. Similarly, arboviruses such as West Nile virus (WNV) and Usutu virus (USUV) are emerging zoonoses. WNV can cause severe neurological diseases in birds, humans, and other animals, while USUV significantly affects blackbird populations and has zoonotic potential, though human cases remain rare. This study investigated avian viruses in 1654 wild birds from 75 species that died at the Wildlife Rescue Center in Vanzago, Lombardy, during 2023–2024. Necropsies were conducted, and virological analyses were performed to detect avian influenza viruses, WNV, and USUV. Among the tested birds, 15 were positive for H5N1 HPAIV clade 2.3.4.4b, all in 2023, including 13 Chroicocephalus ridibundus, one Coturnix coturnix, and one Columba palumbus. Additionally, 16 tested positive for WNV (15 for lineage 2 and one for lineage 1), one for USUV, and 11 co-infections WNV/USUV were recorded in 2023–2024. These findings underscore the importance of avian viral passive surveillance in identifying epidemiological trends and preventing transmission to other species, including mammals and humans.